Analytical/Continental and Derridean: Аналитичко/континентално и Деридаовско - Badarevski, Bobi; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Bobi Badarevski | Боби Бадаревски Title (English): Analytical/Continental and Derridean Title (Macedonian): Аналитичко/континентално и Деридаовско Translated by (Macedonian to English): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 247-267 Page Count: 20 Citation (English): Bobi Badarevski, “Analytical/Continental and Derridean,” translated from the Macedonian by Rodna Ruskovska, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 247-267. Citation (Macedonian): Боби Бадаревски, „Аналитичко/континентално и Деридаовско“, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 247-267.